2002
DOI: 10.1016/s1573-5214(02)80002-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects on productivity and risk factors of Bovine Respiratory Disease in dairy heifers; a review for the Netherlands

Abstract: This paper presents a literature review about the impact of Bovine Respiratory Disease (BRD) on the productivity of dairy heifers and about risk factors for the disease, as far as these are relevant to commercial dairy farming in the Netherlands. The review includes peerreviewed publications over the period January 1980-June 2001 on field studies that quantified the variables of interest. The literature data show that BRD in dairy heifers increases the risk of mortality directly after the disease episode by up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
9
0
2
Order By: Relevance
“…Interestingly, an association was found between median FLP of the herd and BRSV vaccination status. Bovine respiratory syncytial virus is one of the causes for BRD, which from previous studies is known to reduce growth in heifers (Van der Fels-Klerx et al, 2002). As growth and BW at calving are related to milk production (Le Cozler et al, 2008), growth reduction due to not vaccinating against BRSV may explain the found reduction of median FLP of the herd.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, an association was found between median FLP of the herd and BRSV vaccination status. Bovine respiratory syncytial virus is one of the causes for BRD, which from previous studies is known to reduce growth in heifers (Van der Fels-Klerx et al, 2002). As growth and BW at calving are related to milk production (Le Cozler et al, 2008), growth reduction due to not vaccinating against BRSV may explain the found reduction of median FLP of the herd.…”
Section: Discussionmentioning
confidence: 97%
“…Although, the GS's indicate BRD, they do not indicate if the BRD caused an increase in the number of coughs. As the symptoms of BRD vary, it is possible that calves may present with clinical manifestations of BRD, but do not develop a cough (Van der Fels-Klerx et al, 2002).…”
Section: Comparison With Gold Standardsmentioning
confidence: 99%
“…There are substantial costs associated with mortality, antibiotics and/or anti-inflammatory treatment, and poor life-time performance of affected calves. An economic model from 2001 estimated the average loss for a typical Dutch farm with 60% of the heifers affected by BRD at €31.20 per animal (van der Fels-Klerx et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine respiratory disease (BRD) incorporates all possible respiratory diseases in cattle and is characterised by abnormal clinical signs of the respiratory tract [ 1 ]. Bovine respiratory disease refers to bacterial bronchopneumonia that may be complicated by previous, or concurrent, viral or Mycoplasma infection [ 2 ].…”
Section: Introductionmentioning
confidence: 99%